Identifying the impact of new airports on air passenger movement patterns: a study of regional connectivity - Khoiriani, Alifia Dian; Djakfar, Ludfi; Wicaksono, Agus Dwi; Miftahulkhair, Muh (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates the impact of the newly constructed Kediri Airport on air passenger movement patterns in East Java, with a focus on its effect on the existing Juanda and Abdulrachman Saleh Airports. The research addresses the issue of congestion at these primary airports and explores the potential for passenger redistribution with the introduction of a new airport. Using stated preference methods, this study examines how variations in travel costs and time influence passengers’ choices between airports and their shifting patterns. The results indicate that Kediri Airport, due to its improved accessibility and service quality, holds significant potential to divert passenger traffic from Juanda and Abdulrachman Saleh. Projections show that by 2024, Kediri could capture up to 42 % of the passenger traffic currently centered at these primary airports, significantly easing congestion at the main airports. Additionally, the study suggests that the implementation of a Multi-Airport System (MAS) could effectively manage this redistribution, optimizing the use of regional airports and enhancing overall connectivity across East Java. The findings contribute valuable insights into strategic airport network planning and emphasize Kediri’s role in enhancing regional mobility and supporting economic growth. These results are highly relevant for infrastructure planning, where MAS can be leveraged to optimize airport operations and ensure sustainable growth